Maggie's plan [videorecording (DVD)] - Miller, Rebecca, 1962-; Gerwig, Greta; Hawke, Ethan, 1970-; Hader, Bill, 1978- (Sony Pictures Home Entertainment, 2016)
Maggie's plan to have a baby on her own is derailed when she falls in love with John, a married man, destroying his volatile marriage to the brilliant Georgette.